Efektivitas Program Keluarga Harapan (PKH) Di Kecamatan Ratu Agung Kota Bengkulu - Despriyani, Hesti Lira; Imanda, Antonio; Rikardo, Yanuar (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine the “Effectiveness of Program Keluarga Harapan (PKH) in Ratu Agung Sub-District, Bengkulu City. The method used in this research is descriptive qualitative method. Data collection techniques are carried out by means of observation, interviews, and documentation. Data analysis techniques by means of data reduction, data presentation and make conclusion. The informants in this study amounted to 6 people consisting of 2 key informants and 4 main informants. The theory in this study is the theory of effectiveness according to Budiani (in Nuraida 2019: 155), there are 4 aspects used, namely Program Target Accuracy, Program Socialization, Program Objectives, and Program Monitoring. Based on the research results, conclusions can be drawn, namely: 1. Target Accuracy: a. The target recipients of PKH are poor families who meet certain criteria and need social assistance to improve their standard of living, where the PKH target recipients are in accordance with the recipient criteria. b. The intended target is the group or individual who is the main target of an activity or intervention program. In the context of PKH, the intended target is the underprivileged or poor community. However, PKH in Ratu Agung Sub- District has not been running effectively because the program has not been entirely targeted. 2. Program socialization: a. The time of socialization, namely the time of implementation of socialization activities, is carried out every once in a month meeting with Beneficiary Families (KPM) accompanied by PKH assistants. this socialization activity has been running quite effectively. b. The purpose of socialization, namely P2K2 (family capacity building meeting). 3. Program Objectives: The purpose of PKH in Ratu Agung Sub-district, Bengkulu City is to prosper people whose economy is still low and break the chain of poverty, but the objectives of PKH in Ratu Agung Sub-district, Bengkulu City have not been effective because this program has not achieved its main objectives. This can be seen from PKH beneficiary targets, there are still many underprivileged people who are entitled to receive assistance from PKH. 4. Program Monitoring: The implementation of the PKH in Ratu Agung Sub-district, Bengkulu City has so far been running quite effectively.